Short‐term administration of the glucagon receptor antagonist LY2409021 lowers blood glucose in healthy people and in those with type 2 diabetes. Issue 4 (2nd March 2015) - Kelly, R. P.; Garhyan, P.; Raddad, E.; Fu, H.; Lim, C. N.; Prince, M. J.; Pinaire, J. A.; Loh, M. T.; Deeg, M. A.
<x xml:space="preserve">Abstract</x> Aim To describe the clinical effects of single and multiple doses of a potent, selective, orally administered, small‐molecule antagonist of the human glucagon receptor, LY2409021, in healthy subjects and in patients with type 2 diabetes. Methods LY2409021 was administered in dose‐escalation studies to healthy subjects (n = 23) and patients with type 2 diabetes (n = 9) as single doses (Study 1) and daily to patients with type 2 diabetes (n = 47) for 28 days (Study 2). Safety, tolerability, pharmacokinetic (PK) and pharmacodynamic (PD) assessments were made after single doses and in patients receiving once‐daily doses of LY2409021 (5, 30, 60 or 90 mg) for 28 days. Results LY2409021 was well tolerated at all dose levels in both studies. Fasting and postprandial glucose were reduced and glucagon levels increased after single and multiple dosing, with reductions in fasting serum glucose of up to ∼1.25 mmol/l on day 28. Serum aminotransferases increased in a dose‐dependent manner with multiple dosing and reversed after cessation of dosing. Significant glucose‐lowering was observed with LY2409021 at dose levels associated with only minor aminotransferase increases. Conclusion Blockade of glucagon signalling in patients with type 2 diabetes is well tolerated and results in substantial reduction of fasting and postprandial glucose with minimal hypoglycaemia, but with reversible increases in aminotransferases. Inhibition of glucagon signalling by LY2409021 is a promising potential treatment for patients with type 2 diabetes and should be evaluated in longer clinical trials to better evaluate benefits and risks.